Caracterização fenotípica de plantas transgênicas de tomateiro expressando a proteína reprimida por auxina (SIARP) - Estevam, Renata Kaline Souza (2016)
Flowering is a vital process during the plant life cycle and it is characterized by the conversion from the vegetative apical meristem into reproductive meristem due to internal and external factors. Despite the considerable knowledge has been produced in this field, not much is known about the flowering and fruiting process in tomato. Furthermore, previous research from our group has identified a cDNA with homology to AUXIN REPRESSED PROTEIN (ARP) in reproductive subtractive libraries from tomato. In the literature, there are few reports where the ARP gene has been associated to fruit ripening in strawberry, dormancy in pea and pollen maturation in tobacco plants, but it is not clear the ARP protein function yet. Therefore, the aim of this work was to understand the role of ARP protein in vegetative development, flowering and fruit set processes through the loss and/or gain of function using this cDNA in transgenic tomato plants with the overexpression cassette constructs in sense and antisense cDNA orientation. Thus, it was observed some phenotypic and structural modifications in transgenic plants (35S::SlARP antisense and sense) such as early flowering and fruiting that was observed in 35S::SlARP antisense plants from the T1 to T4 progeny when compared to controls plants (with the empty vector and wild type plant). In the histological analysis, it was observed mature ovule in 35S::SlARP antisense flowers (progeny T2 to T4), while for the controls plant it wasn’t observed a mature ovule at the same period of time. The other modification observed was a higher number of lateral buds developed in 35S::SlARP antisense plants (progeny T3 and T4) when compared to 35S::SlARP sense and controls plants. These plants produced branches with leaves, flowers and fruits. Besides, it has been observed some structural changes in the petioles from 35S::SlARP antisense plants, including a high number of vessel elements (xylem and phloem) when compared to 35S::SlARP sense, and to dgt and entire mutants (related to auxin signaling) and controls plants (with empty vector and wild type plant). Therefore, these data suggest that ARP protein may be involved in flowering, fruit set and dormancy of axillary buds in tomato.